Physicochemical and microbial properties of nanopowdered peanut sprout‐supplemented Caciocavallo‐like cheese during ripening. (7th September 2016) - Ko, Eun‐Jung; Chang, Yoon Hyuk; Kwak, Hae‐Soo
Abstract : This study was carried out to investigate the physicochemical and microbial properties of nanopowdered peanut sprout‐supplemented Caciocavallo‐like cheese (NPSCC) during ripening at 14 °C for 6 weeks. The total phenol contents and lactic acid bacteria counts in NPSCC were significantly higher than those in the control, indicating that nanopowdered peanut sprout could potentially be used as a prebiotic and potential source of dietary antioxidants in the dairy products. Thiobarbituric acid values of the cheese were significantly decreased and the production of short‐chain free fatty was not significantly different when nanopowdered peanut sprout was added into the production of Caciocavallo‐like cheese.